1992
DOI: 10.1111/j.1476-5381.1992.tb09081.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of BRL 38227 on neurally‐mediated responses in the guinea‐pig isolated bronchus

Abstract: 1 In guinea-pig isolated bronchus treated with indomethacin (2.8 gM), electrical field stimulation (EFS; 10 Hz, 0.5 ms, 60-70 V, for 10 s) evoked a tetrodotoxin (3 JM)-sensitive, biphasic contraction comprising a rapid, atropine (1 tLM)-sensitive cholinergic response succeeded by a slowly developing, capsaicin (10lM)-sensitive, non-adrenergic, non-cholinergic excitatory (NANCe) response.2 BRL 38227 (0.3-3 AM), salmeterol (0.003-3 pM) and ketotifen (1.0-300 AM) each produced concentration-dependent inhibition o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
10
1

Year Published

1993
1993
2003
2003

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 30 publications
2
10
1
Order By: Relevance
“…We have recently shown that imidazol(id)ine based compounds, such as alinidine, are antagonists of K+ channel openers such as cromakalim, in both vascular and non-vascular smooth muscle (McPherson & Angus, 1989;1990;Challinor & McPherson, 1993). The antagonism displayed by imidazol(id)ine compounds is characterized by a shift to the right in the cromakalim concentration-effect curve associated with a flattening of the curve at higher concentrations ( > 10 9AM) and a reduction in the maximum response (McPherson & Angus, 1989;1990; see also Murray et al, 1989;Good et al, 1992). This type of antagonism was also displayed by the active quaternary ions.…”
Section: The Antagonism Displayed By the Quaternary Ionsmentioning
confidence: 99%
“…We have recently shown that imidazol(id)ine based compounds, such as alinidine, are antagonists of K+ channel openers such as cromakalim, in both vascular and non-vascular smooth muscle (McPherson & Angus, 1989;1990;Challinor & McPherson, 1993). The antagonism displayed by imidazol(id)ine compounds is characterized by a shift to the right in the cromakalim concentration-effect curve associated with a flattening of the curve at higher concentrations ( > 10 9AM) and a reduction in the maximum response (McPherson & Angus, 1989;1990; see also Murray et al, 1989;Good et al, 1992). This type of antagonism was also displayed by the active quaternary ions.…”
Section: The Antagonism Displayed By the Quaternary Ionsmentioning
confidence: 99%
“…MCCAIG and DE JONCKHEERE [3] reported that cromakalim attenuated contractions induced by peripheral vagus nerve stimulation in the isolated guinea-pig trachea, but it had no effect on contractions induced by EFS or exogenous ACh, suggesting a ganglionic effect [3]. By contrast, BURKA et al [4] and GOOD et al [5] found in isolated guinea-pig trachea that cromakalim [4] or lemakalim [5] inhibited EFSinduced contractions more than ACh-induced contractions, suggesting pre-and postjunctional effects. Consistent with the latter results is the observation made in vivo by ICHINOSE and BARNES [6] that cromakalim inhibited bronchoconstriction induced by vagal stimulation more than that induced by exogenous ACh.…”
Section: Effect On Efs-and Ach-induced Contractionsmentioning
confidence: 91%
“…Eur Respir J., 1996Respir J., , 9, 2057Respir J., -2063 In smooth muscle, potassium channel openers (KCOs) increase K + efflux across the cell membrane, resulting in cell membrane hyperpolarization, reduction of Ca 2+ influx through L-type voltage-dependent Ca 2+ -channels [1, 2], and relaxation. There is disagreement about whether the effects of KCOs occur directly at the muscle cell (postjunctional) or at the muscle cell and nerve level (pre-and postjunctional) [3][4][5][6]. For instance, in guinea-pig trachealis the adenosine triphosphate (ATP)-sensitive K + -channel (KATP) opener, cromakalim, affects the excitatory nonadrenergic noncholinergic (eNANC) nervous system [4].…”
mentioning
confidence: 99%
“…Studies in vivo have activators will attenuate the release of neuropeptides (such as confirmed that when administered by a variety of different substance P and neurokinin A) from excitatory nonroutes such compounds protect animals from the bronchoadrenergic, non-cholinergic (eNANC) unmyelinated nerves spastic effects of a variety of stimuli (Arch et al, 1988; (C fibres) (Ichinose & Barnes, 1990; Lewis & Raeburn, 1990;Paciorek et al, 1990a;Bowring et al, 1991;Raeburn & Burka et al, 1991;Good et al, 1992). In particular, inhibi- Karlsson, 1991;Englert et al, 1992).…”
Section: Introductionmentioning
confidence: 99%